Effect of Musical Therapy on Malondialdehyde Levels on Male Mice Brain Tissue - Farindra, Irmawan; Muhammad, Akbar Reza; Algristian, Hafid; Rusdi, Warda Elmaida; Yuniati, Dyah (Jurnal Medis Islam Internasional, 2024)
Introduction: An example of a non-pharmacological therapy that is currently being developed is music therapy. The serenity created from classical music and murottal therapy is good for therapy performance, accelerating the healing process, and also reducing stress level. Objective: The aim of this study was to examine the effects of classical music "Mozart" and Murottal Al-Qur’an therapy on mouse malondialdehyde levels Methods: This study used 24 male BALB/c strain mice (10-12 weeks), in a true experimental setting using the Post Test Only Control Group Design. Four groups of mice were created: K (control), P1 (murottal Al-Qur'an), P2 (classical music "Mozart"), and P3 (combination therapy). SPSS 24 was used to analyze the data with a significance P < 0.05 Results: According to study findings, the P2 group had the highest average malondialdehyde level meanwhile the lowest average malondialdehyde levels was found in Group P1. The test results showed no significant relationship (p = 0.213) Conclusions: The findings of this study showed that there was no significant correlation between malondialdehyde levels when "Mozart" classical music and Murrotal treatment were given. The group who received the classical music "Mozart" nevertheless, had higher malondialdehyde levels, according to the findings.